Optimizing cultivars enhances the climate resilience of oat production across China under future climate change - Tang, Jianzhao; Bai, Huizi; Yang, Huiyong; Zhang, Xinjun; Guo, Fenghua; Zhou, Haitao (Frontiers in Agronomy, 2025)
IntroductionOat (Avena sativa L.) is a vital grain and forage crop that supports global food security and sustainable diets. A comprehensive understanding of the adaptive potential of oat to climate change is urgently required in order to develop effective strategies for ensuring future agriculture and food security.MethodsIn this study, using the Agricultural Production Systems Simulator (APSIM)-Oat model and the CMIP6 shared socioeconomic pathway (SSP) scenarios, we investigated potential adaptation strategies through cultivar optimization across China, including Northeast China (NEC), North China Plain (NCP), Northwest China (NWC), and Southwest China (SWC). ResultsUnder future climate scenarios, the rainfed oat biomass and yield are projected to decrease in the 2030s, with improvements emerging in the cooler northern regions such as NEC by the 2060s, with the southern regions including NCP, NWC, and SWC continuing to experience declines. Similar trends are observed under irrigated conditions. Cultivar optimization shows strong regional and water management specificity, and early-maturing cultivars are recommended for NEC under rainfed conditions, whereas middle- and late-maturing types suit NCP, SWC, and NWC. Under irrigation, early-maturing cultivars perform better across NEC, NCP, and NWC, with middle-maturing cultivars remaining preferable in SWC.DiscussionAdopting optimal cultivars effectively mitigates the yield losses in vulnerable regions such as SWC and enhances the yield gains in other regions under both rainfed and irrigated systems. These findings highlight the importance of region-specific cultivar optimization in sustaining oat production, supporting climate-resilient agriculture, and safeguarding long-term food security.